Substantiation and working out of recreation health related technology on the basis of health related hiking and orienteering for junior school age children - N.N. Goncharova; H.A. Butenko (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose: to study role of health related hiking and orienteering in improvement of children's physical conditions. Material: 163 children of 7 - 10 years old age participated in the research (82 boys and 81 girls). Tests for assessment of physical condition, physical health, adaptation reserve potentials and motor functioning of junior schoolchildren were used. Results: It was found that 46,01% of pupils can be considered healthy. Accordingly more than half (53,99%) have not infectious diseases. Among them nosologies of musculoskeletal apparatus prevail. In academic day with physical culture lesson average and high levels of motor functioning prevail (61,36%). Recreation health related technology on the basis of health related hiking and orienteering has been theoretically substantiated and worked out. Its structural components and content have been described. Realization of recreation health related technology is envisaged to be in three stages. Most of classes shall be in the open air. Conclusions: low level of adaptation reserve potentials and physical health of children have been determined that points at demand in health related measures in junior schoolchildren's physical education.